2017
DOI: 10.3847/1538-4357/aa6f0e
|View full text |Cite
|
Sign up to set email alerts
|

Mass-loss Rates from Coronal Mass Ejections: A Predictive Theoretical Model for Solar-type Stars

Abstract: Coronal mass ejections (CMEs) are eruptive events that cause a solar-type star to shed mass and magnetic flux. CMEs tend to occur together with flares, radio storms, and bursts of energetic particles. On the Sun, CME-related mass loss is roughly an order of magnitude less intense than that of the background solar wind. However, on other types of stars, CMEs have been proposed to carry away much more mass and energy than the time-steady wind. Earlier papers have used observed correlations between solar CMEs and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 124 publications
5
46
1
Order By: Relevance
“…The presence of such fields is now definitively established for active M dwarfs (Shulyak et al 2017;Kochukhov & Shulyak 2019) and T Tauri stars (Sokal et al 2020). This suggests that local field strength is not limited by the confinement of magnetic flux tubes by the photospheric gas pressure as was repeatedly assumed in the past (Saar & Linsky 1986b;Cranmer 2017;See et al 2019).…”
Section: Correlation With Stellar Parametersmentioning
confidence: 75%
See 1 more Smart Citation
“…The presence of such fields is now definitively established for active M dwarfs (Shulyak et al 2017;Kochukhov & Shulyak 2019) and T Tauri stars (Sokal et al 2020). This suggests that local field strength is not limited by the confinement of magnetic flux tubes by the photospheric gas pressure as was repeatedly assumed in the past (Saar & Linsky 1986b;Cranmer 2017;See et al 2019).…”
Section: Correlation With Stellar Parametersmentioning
confidence: 75%
“…Information on the magnetic filling factors determined within this framework (provided that f can be reliably separated from B) is important for understanding a range of processes taking place in active cool stars (e.g. Montesinos & Jordan 1993;Cranmer & Saar 2011;Cranmer 2017;See et al 2019).…”
Section: Magnetic Spectrum Synthesismentioning
confidence: 99%
“…Being suddenly exposed to the stellar radiation pressure (and stellar wind) for the first time, the overdense small Qrp , wherė M is the mass-loss rate, vsw is the wind velocity, c is the speed of light, L is the stellar luminosity, and Qsw and Qrp are the efficiency factors for stellar wind and radiation pressure (assumed to be 1). Adopting a mass-loss rate of 2×10 −10 M yr −1 for a young solar-type star during a CME event (Cranmer 2017) and a wind velocity of 2000 km s −1 , this ratio is ∼20 during the enhanced stellar wind phase. dust grains (called seeds by Chiang & Fung (2017)) would collide with other particles within the cloud to generate grains of similar sizes (β-meteoroids) in an exponentially amplifying avalanche (Chiang & Fung 2017; see further discussion in Section 6.3).…”
Section: Radiation Pressure and Stellar Windmentioning
confidence: 99%
“…Our study has excluded only the full halo CMEs for which the mass is underestimated and often some of their mass could be hidden behind the occulter of the coronagraphs. The study of Cranmer (2017), by excluding the CMEs labeled as "poor" events and the ones listed without masses in the CDAW catalog, have also found that the CMEs contribute only about 3% of the background solar wind mass flux during the maximum of the cycle 23. However, in a few studies, the contribution of CMEs to solar wind mass flux in the ecliptic is found to be around 15% during the maximum of the cycle and around 3% at the minimum of the cycles (Hildner 1977;Jackson & Howard 1993;Webb & Howard 1994).…”
Section: Solar Wind Mass Loss Rate and Proxies Of Solar Cyclementioning
confidence: 99%